Funeral of choice: Ritualizing of death between tradition and innovation (Nordic Journal of Practical Theology, 2024)
The article discusses how funeral practices develop between being binded by tradition and being seen as places for personal expression and free choice. Building on research that shows how tradition is the main reason for people to choose a church funeral, the analysis explores the conceptualisation and role of tradition in the material. Further, we look into how newer funeral logics come to expression, and how different actors in the practice field understand and negotiate these concepts. The article argues that tradition and personalised choice are complex phenomena, and that there is a risk that they are compared before they are understood. We find that tradition for many families is an important concept but their articulation of what it means is ambigous. Further, families perceive newer funeral practices not so much within logics of choice as arenas for expression of meaning. Both funeral directors and clergy meet the new development with varied opinions and strategies, but where tradition and innovation are in constant interplay.